Comparison of Mucosal, Subcutaneous and Intraperitoneal Routes of Rat Leptospira Infection. - Anne-Laure Zilber; Patrick Belli; Delphine Grezel; Marc Artois; Angeli Kodjo; Zoheira Djelouadji (Public Library of Science (PLoS), 2016)
Leptospirosis is a zoonosis found worldwide that is caused by a spirochete. The main reservoirs of Leptospira, which presents an asymptomatic infection, are wild rodents, including the brown rat (Rattus norvegicus). Experimental studies of the mechanisms of its renal colonization in rats have previously used an intraperitoneal inoculation route. However, knowledge of rat-rat transmission requires the use of a natural route of inoculation, such as a mucosal or subcutaneous route. We investigated for the first time the effects of subcutaneous and mucosal inoculation routes compared to the reference intraperitoneal route during Leptospira infection in adult rats. Infection characteristics were studied using Leptospira renal isolation, serology, and molecular and histological analyses. Leptospira infection was asymptomatic using each inoculation route, and caused similar antibody production regardless of renal colonization. The observed renal colonization rates were 8 out of 8 rats, 5 out of 8 rats and 1 out of 8 rats for the intraperitoneal, mucosal and subcutaneous inoculation routes, respectively. Thus, among the natural infection routes studied, mucosal inoculation was more efficient for renal colonization associated with urinary excretion than the subcutaneous route and induced a slower-progressing infection than the intraperitoneal route. These results can facilitate understanding of the infection modalities in rats, unlike the epidemiological studies conducted in wild rats. Future studies of other natural inoculation routes in rat models will increase our knowledge of rat-rat disease transmission and allow the investigation of infection kinetics.